ChemInform Abstract: Facile and Highly Diastereoselective Synthesis of syn‐ and cis‐1, 2‐Diol Derivatives from Protected α‐Hydroxy Ketones. Issue 17 (April 2016) - Jahn, Emanuela; Smrcek, Jakub; Pohl, Radek; Cisarova, Ivana; Jones, Peter G.; Jahn, Ullrich
Abstract: A new and diastereoselective method for the synthesis of 1, 2‐diols from Tmp‐protected α‐hydroxyketones is developed.